The development of flashcard media to improve students’ english vocabulary in english lessons at Islamic elementary school - Asrindah Nasution; Rani Rahim (University of Muhammadiyah Malang, 2022)
This study aims to determine how to develop appropriate and effective flashcards and to find out whether flashcards can improve students' English vocabulary. The developed media is flashcards. The subjects in this study were fourth-grade students of SD MIS Nurul Hidayah Medan. This type of research was R & D research using a 4-D model. Finding out the feasibility of the media is obtained from an expert validator. Meanwhile, finding out the effectiveness of the media is obtained by testing the media. The trial was carried out twice. The trial was conducted on fourth-grade students consisting of 30 students. Based on the conclusion of the expert, it was stated that the flashcard is worthwhile and effective. While based on the results of the students’ assessment test on the flashcard showed that there was an increase in students' English vocabulary in the first and second trials. Thus, it can be concluded that the development of flashcard as media is feasible and effective for students to use in the teaching and learning process.